Working memory task performance on prefrontal cortex activation: An optical neuroimaging study - Hani, A.F.M. (Institute of Electrical and Electronics Engineers Inc., 2017)
Cognitive brain functions such as language, comprehension, planning and reasoning require working memory (WM), a temporary storage which holds a limited information for instant manipulation. It is hypothesized that WM performance play an important role in altering the brain activity on the prefrontal cortex (PFC) region. Here, Optical Topography Functional Near Infrared Spectroscopy (OT-fNIRS) was used to measure the haemodynamic responses on the PFC during n-back tasks with incremental WM loads (N= 0, 1, 2). Behavioural and functional data were acquired from 14 male university student volunteers to examine the effects of n-back WM task performance. Subjects were categorized as high performance (>90 accuracy for all tasks) and normal groups for further analysis. Behavioural results showed that the normal group responded slower, regardless of the given WM load. During 2-back task, subjects in normal group performed significantly poor (low accuracy, p<0.05) as compared to high performance (HP) group. Functional results revealed that the HP group exhibits increasing oxygenated haemoglobin (OxyHb) activation in the dorsolateral prefrontal cortex (DLPFC) region while proceeding from 0-back task to 2-back task. Conversely, the normal group showed increase OxyHb activation from 0-back task to 1-back task, but significantly reduced OxyHb activation (p<0.05) when advanced to 2-back task. This suggests that higher brain activation for a higher WM load is only true if the task performance is maintained. Besides, higher OxyHb activation in the DLPFC (N= 1, 2) and Frontal Pole regions (N= 0, 1, 2) are found within the normal group, as compared to HP group. These indicate that the normal group subjects spent more mental effort to cope with the given tasks, as evidenced from increased OxyHb activation and longer response time, yet declined in task accuracy. © 2016 IEEE.